Rumen ciliates (Alveolata, Ciliophora) associated with goats: checklist, geographic distribution, host specificity, phylogeny and molecular dating - Da Silva, Zacarias Rosalina João; Cedrola, Franciane; Rossi, Mariana Fonseca; Costa, Fabiola Da Silva; Dias, Roberto Júnio Pedroso (Zootaxa, 2022)
Although the diversity (~35 species) and worldwide distribution of goats (Ruminantia, Bovidae, Caprinae) are significant, studies on the diversity of symbiont ciliates in these mammals are scarce in comparison to other ruminants. The present work is a review and checklist of species based on taxonomic, morphologic, and ecologic studies of rumen ciliate protozoa in goats, presenting geographic distribution and hosts, as well as estimating the macroevolutionary relationships of the species observed in the studies. To that end, all of the available literature on databases was reviewed, the schematic drawings were made based on information present in the original description of the taxa, and the phylogenetic relationships were inferred based on Maximum Likelihood and Bayesian Inference analyses. According to our review, 72 species and 14 genera of ciliates have been associated with goats. Through the analysis of the association between ciliate genera and caprine hosts, it was shown that ciliates are more associated with domestic animals (Capra hircus—14 genera) than wild ones (Rupicapra rupicapra—six genera, Capra ibex—one genus, Capra pyrenaica—one genus). Thirteen countries were identified in the distribution map as having had reports of ciliate species associated with goats. The interaction networks of ciliates and their hosts showed that the species of ciliates associated with goats also occur in other herbivore mammal species. The recovered phylogenetic hypotheses show that the ciliate species in goats form a non-monophyletic group with maximum and minimum ages of ~8.2My and ~2.4My. We have also found that a large portion of the studies on the diversity of ciliates in goats does not employ all necessary techniques in an integrative way, despite it being essential for detailed descriptions and better knowledge of this fraction of biodiversity.